TVET Sector Assessment of skills mismatch in Caraga Region - Reyes, Rachel G.
This study was conducted to analyze the demand and supply of skills, and the issues that arise that give evidence to skills mismatch particularly in Technical Vocational Education and Training (TVET) sector in Caraga Region. This study was designed to provide the status of the TVET sector in terms of its efficiency in meeting the demand of the business sectors. At this point, a secondary data analysis was conducted to show the relationship of the factors included in the study. Factors included are TVET enrolment, graduates, tuition fee of both TVET and Higher Education Institutions (HEIs), and gross regional domestic product. An interview survey was also utilized to cater to the other factors involved in the decision making of the key informants: TVET students, TVET providers and user or business firms employing TVET graduates. To present further the strength of association between the factors included, a correlation formula was employed. Based from the deficiencies of TVET providers in terms of faculty and materials, and the feedback from both the business sectors and the students, this study asserts that the Technical Vocational and Educational sector (TVET) has not been efficient in meeting the demands of the business sectors in Caraga region.